Tourette-like syndrome secondary to Kleefstra syndrome 1 with a de novo microdeletion in the EHMT1 gene - Mengyue Niu; Yanjing Li; Shikun Zhan; Bomin Sun; Jun Liu; Yiwen Wu (BMC Neurology, 2023)
Abstract Background Gills de la Tourette syndrome (TS) is a childhood-onset neurodevelopmental disorder manifested by motor and vocal tics. Kleefstra syndrome 1 (KS1), a rare genetic disorder, is caused by haploinsufficiency of the EHMT1 gene and is characterized by intellectual disability (ID), childhood hypotonia, and distinctive facial features. Tourette-like syndrome in KS1 has rarely been reported. Case presentation Here we describe a 7-year-old girl presenting involuntary motor and vocal tics, intellectual disability, childhood hypotonia, and dysmorphic craniofacial appearances, as well as comorbidities including attention deficit-hyperactivity disorder (ADHD), obsessive-compulsive disorder (OCD), and self-injurious behavior (SIB). The patient’s CNV-seq testing revealed a de novo 320-kb deletion in the 9q34.3 region encompassing the EHMT1 gene. Conclusions This is the first case reporting Tourette-like syndrome secondary to KS1 with a de novo microdeletion in the EHMT1 gene. Our case suggests TS with ID and facial anomalies indicate a genetic cause and broadens the phenotypic and genotypic spectrum of both TS and KS1.